A GIS model analysis on the prediction of socio economic impacts - Asmawi, M. Zainora; Abdullah, Muhammad Faris; Abdullah, Alias; Shahbudin, Nur Azraei (Malaysia Remote Sensing Agency, 2018)
The recent global changes in GIS technology advancement have significantly influenced the spatial development of urban areas concerning its impacts on the surroundings. This paper addresses the formation of a GIS-based technology in predicting the potential socio-economic consequences due to the development. The approach employed was extensively based on a series of baseline data, models, spatial and statistical analysis to develop a prototype GIS system in predicting future socio-economic impacts, called Development Impact Assessment. Furthermore, this paper also uses a practical technique of ‘what if?' scenario which can assist in charting possible complicated linkages between criteria from multiple sources. The system consists of some selected vital components of the socio-economic, including car parking requirement, a projection of commercial floor space and estimated job creation. The results demonstrate the strengths and abilities of GIS to provide a spatial analysis showing the distribution of the socio-economic impacts in urban planning system that could assist the local planning authority in creating a sustainable living environment. Thus, the GIS system also carries the value of incorporating the complexity of wicked problems existed in urban planning into a technology-based device. This GIS model analysis is efficient to determine the sustainability of urban areas, taking into the consideration the challenges that we face today